Penyuluhan Hukum di Kelurahan Pannampu Makassar: Menyingkap Hak Anak dan Perempuan Pasca Perceraian di Wilayah Urban - Aulia Rifai; Ilham Arisaputra; Amaliyah Amaliyah; Khulaifi Hamdani; Muhammad Narya Febrian (Jurnal Pengabdian Masyarakat Nusantara, 2024)
The increasing divorce rate in South Sulawesi, particularly in Makassar, poses significant challenges to the protection of children's and women's rights. This study aims to enhance community understanding in Panampu Village regarding these rights post-divorce through legal counseling. The method used is Asset Based Community Development (ABCD), which involves the community in every stage of the activity, from problem identification to evaluation. The counseling event was held on November 15, 2024, attended by 50 participants, and the pre-test results indicated a low level of understanding. However, after the counseling, the post-test results showed a significant improvement in understanding, with all participants answering correctly regarding the rights of children and women. This activity is expected to contribute to increased legal awareness and the protection of children's and women's rights in the community